Pengaruh Persepsi terhadap Minat Memilih Baitul Maal Wat Tamwil (BMT) Insani Padangsidimpuan - Fadhlan Shubuhanda; Fatahuddin Aziz Siregar; Damri Batubara (Journal of Islamic Social Finance Management, 2020)
AbstractEnvironmental Community V Sidangkal Subdistrict, South Padangsidimpuan Subdistrict is classified as a pluralistic society in terms of religion. This research was conducted to determine whether there is an effect of perception on the interest in choosing Baitul Maal wat Tamwil (BMT) Insani Padangsidimpuan, and to analyze the selection criteria that were considered in selecting BMT Insani Padangsidimpuan and to analyze people's attitudes. The sampling technique used in this study was saturated sampling. Saturated Sampling is a sampling technique when all members of the population are used as samples. Another term saturated sample is census, where all members of the population are sampled. The results showed that there was an effect of perception on the interest in choosing BMT Insani Padangsidimpuan, or from the results of the coefficient of determination showed that the value of R = 0.564 and R x R = R2 was 0.318 which stated that the X (Perception) variable contributed to the Y (Interest) variable by 31, 8%, meaning that the variable X (Perception) can affect the variable Y (Interests). And 68.2% of people's perceptions are influenced by other factors. Keywords: Perception, Interests, and Baitul Maal wat Tamwil (BMT).